PEDAGANG KAKI LIMA (PKL) SEBAGAI ALTERNATIF SOLUSI DALAM MENGATASI KEMISKINAN DAN PENGANGGURAN - Tjutju Fatimah (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2011)
Solution to overcome the unemployment problems can be done by the way of making someone who expert in entrepreuneur. Because an entrepreuneur hardly assists government in chartered investment counsel recovery. Because they stand in adding national production, creates job activity opportunity, assists government to lessen unemployment, assists government in development averaging, adds resource of stock-exchange for government, adds source of national income with paying tax, and assists government in enriching nation.